PROSES PENDISTRIBUSIAN SAYURAN DAN BUAH DI AGROWISATA PUNCAK BUKIT CATU TABANAN-BALI: The Distribution Processing of Vegetables and Fruit in Agrowisata Puncak Bukit Catu Tabanan-Bali - Lailansia Wahyu Prasiwi, Rosiana Ulfa, Bagus Setyawan (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2021)
Fruit and vegetable commodities are one source of accelerated growth in the agricultural sector due to the elastic nature of demand for income. Based on the availability of land, this commodity in the Puncak Bukit Catu Bedugul Agrowisata is still possible to be developed on a wider scale. The large number and types of products produced, cause increased competition among companies producing similar products, so companies are also encouraged to be able to improve the quality and quantity of their products and carry out marketing concepts quickly and precisely. The purpose of this study is to determine the process of packaging vegetables and fruit to the distribution site. The method used by collecting data through direct observation, namely direct interviews with all related parties, direct practice, and documentation. The result obtained from this study is that the packaging of vegetables and fruit is carried out using PE plastic of the LDPE type and the distribution process uses box cars and pick-ups equipped with tarpaulins to avoid the sun.